Intervention in International Navigation: A Case Study of Seizure of Oil Tankers by States in the Implementation of Domestic and International Cross-Border Sanctions - Reyhane Derogari; Hatam Sadeghi Ziyazi; Somayehsadat Mirilavasani (پژوهشهای حقوقی)
Exercising the jurisdiction of states in different maritime areas is a subject that has always been a source of controversy throughout the history of the international law of the seas. The efforts that have been made to increase these qualifications and the restrictions that have been applied to regulate them. However, on what basis such an increase and limitation of jurisdiction is done, it has caused many disputes. On the one hand, states emphasize the unquestionable principle of freedom of navigation contained in the UNCLOS, and on the other hand, by entering into some agreements to inspect and seize ships, they limit and, as a result, interfere with navigation. Today, in addition to the traditional interventions and restrictions on navigation that are stated in article110 of UNCLOS, we are facing emerging issues in the field of seas, which can be the reason for the intervention of ships in order to maintain international peace and security, interests and internal laws of states. Providing and implementing sanctions is an important part of this position. The main question is how to justify the intervention of international navigation in the implementation of cross border sanctions? In the present article, which is written with a descriptive analytical method and using library sources, by examining the legal bases of intervention in shipping and the implementation of economic sanctions in this regard, it can be concluded that today the acceptance and implementation of international agreements that it is considered as one of the main policies of governments, it it has been able to remove the interventions towards the ships from the framework of the Convention on the Law of the Sea and puts the implementation of unilateral policies of the governments such as the application of cross border sanctions, which is a sign of deviation from important principles such as the principle of freedom of navigation.